CARBONATITIC MELTS IN CUBOID DIAMONDS FROM UDACHNAYA KIMBERLITE PIPE (YAKUTIA): EVIDENCE FROM VIBRATIONAL SPECTROSCOPY - Zedgenizov D.A.; Shatsky V.S.; Sobolev N.V.; Kagi H. (My University, 2004)
Micro-inclusions (1-10 μm) in 55 diamonds of cubic habit from the Udachnaya kimberlite pipe have been studied using vibrational spectroscopy. This has revealed a multiphase assemblage in cuboid diamonds from the Udachnaya kimberlite pipe. This assemblage includes carbonates, olivine, apatite, graphite, water and silicate glasses. The micro-inclusions preserve the high internal pressure and give confidence that the original materials were trapped during growth of the host diamond. The internal pressures, extrapolated to mantle temperatures, lie within the stability field of diamond and the relatively low temperatures are typical for the formation of cuboid diamonds. In contrast to previously reported data for African diamonds, the micro-inclusions in the cuboids from Udachnaya are extremely carbonatitic in composition (H2O/(H2O+CO2) ≈5-20%) with the observed assemblage of microinclusions similar to some types of carbonatites. The low water and silica content testify that the material in the micro-inclusions of the Udachnaya diamonds was near-solidus carbonatitic melt. Vibrational spectroscopy has provided the evidence of carbonatitic melts in cuboid diamonds.